Pluralime dan Hubungan antar Umat Beragama dalam Tafsir Al Qur’an - Siswati, Vialinda (Qolamuna : Jurnal Studi Islam, 2018)
Pluralism has always been a hot topic discussed by political elite figures especially the year before the presidential election, in fact if we look at pluralism as nothing new for Muslims but this has happened in the time of the Prophet Muhammad, there is also evidence history where the existence of the Medina Charter Agreement was an historic event for Muslims and was further strengthened by the verses of the Qur'an which explained how pluralism as a form of respect and respect for other religious followers without having to mix religious theology, sometimes pluralism is misinterpreted by excessive means by them so that they seem to mix various ways of worship in religion and we all know that Indonesia also has pluralism in worship and that is all a form of Indonesia's wealth. Key words : Pluralisme, Tafsir Al Qur’an